Red bat fatality: Geographic extents through deuterium and niche models. Issue 6 (30th July 2019) - Murtaugh, Rachael A.; Capparella, Angelo P.; Kostelnick, John C.; Johnson, Greg D.
ABSTRACT: Bat fatality at wind energy facilities is a conservation issue, but its effect on bat populations is difficult to estimate. We have little understanding of wind turbine effects on bat population persistence, in part because we have poor knowledge of bat migration pathways and hence the source populations for individual fatalities. We used deuterium ratio analysis combined with genetic algorithm for rule‐set prediction and the web‐based isoscapes modeling, analysis, and prediction in a geographic information system environment as a novel approach. Our objectives were to explore the utility of these methods together and map the geographic extents of eastern red bat ( Lasiurus borealis ) specimens salvaged in 2008–2010 from a single, 92‐km 2 wind energy facility in Illinois, USA. Results indicate that combining these methods can be successful and support their use with species where ranges may be less well defined. Because of the migratory nature of this species and the range of deuterium values of pixels in our isotope model, we predicted that 18% and 82% of the specimens would have isotope results inside and outside of the wind facility's isocline respectively. We concluded that 71.4% of the specimens had isotope signatures placing them outside the wind facility's isocline. It could be argued that the wide distribution of bat fatalities dilutes the overall effect of those fatalities on the bat species; however, if other facilities show a similar pattern, each facility could have cumulative and far reaching population‐level effects. © 2019 The Wildlife Society. Abstract : The combination of isotopes and niche modeling, using existing museum and wind farm‐salvaged specimens, represents a viable alternative for characterizing the movement patterns and ranges of migratory bat species. Furthermore, the combination of these methods is an option for other species whose ranges are less well known.